Why Don’t You Let the Light In? Developing Radiant Patterns for a Critical Game Aiming Player Empowerment - Filho, Luiz Santos; Carneiro, Nayana; Sousa Junior, Alairton; Darin, Ticianne (Journal on Interactive Systems, 2026)
The exponential growth of the digital games industry has intensified the use of Deceptive Patterns (DPs) – design strategies that, while profitable, undermine players’ psychological well-being by frustrating their needs for autonomy, competence, and relatedness, as defined by Self-Determination Theory (SDT). In response, ethical alternatives, such as Radiant Patterns (RPs), have been proposed; however, they have remained mainly theoretical. This study addresses this gap with a twofold contribution. First, it details the refinement and operationalization of the RPs concept, transforming it from an abstract idea into a structured framework for well-being-oriented design. Second, it presents the development and evaluation of The Good Dev (TGD), the first critical game to implement this refined framework. TGD was evaluated in two phases (Alpha and Beta tests) using a mixed-methods approach, including validated instruments and semi-structured interviews. Findings reveal that while players recognize DPs, they are unaware of the psychological impact these patterns have on player well-being. The game demonstrated high playability and engagement, proving effective in fostering critical reflection on design ethics. Ultimately, this study highlights the potential of combining the RP framework with critical gameplay to empower players and contribute to healthier digital gaming environments.